ANÁLISIS DEL IMPACTO EN COSTA RICA DE LOS CICLONES TROPICALES OCURRIDOS EN EL MAR CARIBE DESDE 1968 AL 2007 - Alfaro Martínez, Eric J. (2010)
The study of tropical cyclones activity in the Caribbean and their historic characterization in the Central American region is a basic element to mitigate their impact over different regions of the isthmus. Years with high and low tropical cyclone impacts in Central America were defined, considering variables like track, residence time near the isthmus and the annual occurrence of cyclones in the basin. The analysis showed that tropical cyclones are more likely to occur near Central America during August-September-October. Also, positive sea surface temperature and relative humidity at 700hPa and negative sea level pressure anomalies at the Tropical North Atlantic were observed for the years that showed high occurrences of tropical cyclones near Central America. Additionally, Costa Rica has a good natural disasters data base, related with events that affected specific locations and several socioeconomic sectors like agriculture, energy and transport. This data base, allowed the study of disasters in Costa Rica related with tropical cyclones during the last four decades. The analysis showed a trend in the annual number of impacts related with hydro-meteorology causes that cannot be explained by climate trends only. That means that other variables like those related with socioeconomic aspects should be included in the analysis to explain this variability and their associated impacts.